MAQĀṢID AL-SYARĪ’AH DALAM TINJAUAN PEMIKIRAN IBNU ‘ĀSYŪR DAN JASSER AUDA - Mohammad Fauzan Ni’ami; Bustamin Bustamin (Institut Agama Islam Negeri Batusangkar, 2021)
This paper examines the comparative maqāṣid al-syarī’ah in the thoughts of ibn 'āsyūr and jasser auda, preceded by examining the construction of maqāṣid al-syarī’ah thinking of ibnu' āsyur and jasser auda which contains the background of thought, maqāṣid al- theory. shārī 'ah, and the method of determining the maqāṣid al-syarī’ah. This paper also analyzes the advantages and disadvantages of the similarities and differences between the maqāṣid al-syarī’ah which was initiated by Ibn 'Āsyūr and Jasser Auda. Not to forget that this type of research is library research using a comparative approach. The results show that the similarities of maqāṣid al-syarī’ah ibnu āsyūr and jasser auda both make constructive criticism of the traditional model maqâsid for various reasons, while the difference is that the concept of maqāṣid asy-syarīʻah is offered with their background backgrounds. The weaknesses of the maqāṣid al-syarī'ah Ibn 'Āsyūr are that the big idea is still the same as that of Imam al-Shāṭibī such as the method of istiqrā' and the way of expressing the aims of shari 'by paying attention to the form of amar, nahi which has a clear start, while the lack of maqāṣid al-syarīʻah Jasser Auda is in the author's opinion setting aside the turast tradition.